OPTIMALISASI PENGELOLAAN DANA ZAKAT PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN PROBOLINGGO (Study Kasus BASNAZ Kec. Krejengan) - Maula Nasrifah (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2023)
The purpose of this study was to determine the role of the Probolinggo Regency Amil Zakat Agency (BAZNAS) in optimizing the management of zakat funds with a case study at BAZNAS Kec. krejengan. The writing method in this study uses a qualitative approach with descriptive analysis methods. Collection techniques with observation data, documentation, and interviews. The data sources in this study are primary and secondary data sources using interview techniques. The results in this study indicate that in an effort to optimize the management of Zakat funds, BAZNAS Probolinggo Regency makes efforts to distribute zakat funds using two mechanisms, namely the traditional creative consumptive description and the creative productive descriptive. Keywords: Optimization, Management, Distribution, Zakat, BAZNAS